Pengaruh Kepemimpinan Inovatif Terhadap Kinerja Perusahaan Di Pt JGC Indonesia - Tiara, Helviana; Garnida, Agus (Jurnal Sekretaris dan Administrasi Bisnis, 2023)
Company’s performance is one of indicator which reflect the success that has been achieved by a company in a specific time. One of factor that influence to the company’s performance is the leadership style. An innovative leader tends to strive to maximize their member’s potency, supporting and facilitating their member in order to develop themselves and fulfilling the Company’s expectation through a better performance. The purpose of this research is to comprehend the influence of an innovative leadership to enhance company’s performance. Population of this research are the managerial level in PT JGC Indonesia. In this research, researcher was involving 100 respondents. The analysis that utilized by this research is a Structural Equation Model (SEM) approach supported by Smart PLS application. The hypothesis result for the Influence of Innovative Leadership to the Company’s Performance produced a Beta Positive score (0.842) with T Statistic 19.456 (p>1,96) and p values 0.000 (p<0.05) then produced a significant positive influence between the variable of innovative leadership to the Company’s performance. It means that the better and the more innovative the leader, the Company’s performance will enhance. The role of an innovative leadership to their employee is required to enhance the employee’s performance so that the Company’s performance will be excellent eventually.